1986
DOI: 10.1084/jem.164.6.1988
|View full text |Cite
|
Sign up to set email alerts
|

Human T cell activation. III. Rapid induction of a phosphorylated 28 kD/32 kD disulfide-linked early activation antigen (EA 1) by 12-o-tetradecanoyl phorbol-13-acetate, mitogens, and antigens.

Abstract: With human T cells activated by 12-o-tetradecanoyl phorbol-13-acetate (TPA) as immunogen, an IgG2a mAb, early activation antigen 1 (EA 1), was generated against a 60-kD protein with disulfide-linked 28-kD and 32-kD subunits. Both subunits were phosphorylated. The antigen, EA 1, was readily detected on approximately 60% of isolated and cryopreserved thymocytes, as determined by indirect immunofluorescence. A low level of EA 1 expression was detectable on 6-7% of blood lymphocytes. TPA-activated T cells expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
147
0
2

Year Published

1996
1996
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(157 citation statements)
references
References 46 publications
8
147
0
2
Order By: Relevance
“…However, the same multi-phasic pattern of TCR expression was observed. We studied another surrogate marker of TCR engagement, CD69, which is transiently up-regulated after TCR signaling [41,42]. In C10.4 + /1.11 TEC cultures a rapid increase of CD69 levels was observed at both AttM concentrations (610 pM and 625 nM) (Fig.…”
Section: Thymocyte Selection Is Multi-phasicmentioning
confidence: 99%
“…However, the same multi-phasic pattern of TCR expression was observed. We studied another surrogate marker of TCR engagement, CD69, which is transiently up-regulated after TCR signaling [41,42]. In C10.4 + /1.11 TEC cultures a rapid increase of CD69 levels was observed at both AttM concentrations (610 pM and 625 nM) (Fig.…”
Section: Thymocyte Selection Is Multi-phasicmentioning
confidence: 99%
“…The CD69 molecule has been reported to be an early activation antigen in lymphoid cells (4,5). The expression of CD69 in T cell subsets was analyzed by threecolor flow cytometry with PE-CD4 or PE-CD8, peridinin chlorophyll protein (PerCP)-CD20 and FITC-CD69 (Leu23 [IgGi, Becton-Dickinson]) antibodies.…”
Section: 'mentioning
confidence: 99%
“…Up till now, the most commonly used cell surface marker to detect recently activated lymphocytes and other immune cells has been CD69. [34][35][36] Although no direct comparison between the two markers has been performed, data from the literature indicate that CD69 could be far less specific than TNFa, because a significant proportion of CD69 þ cells do not produce cytokines. 37 Although TNFa secretion pathways have been reported that are independent of TACE, 38 most TNFa molecules are produced as cytoplasmic membrane proteins that are rapidly cleaved into a soluble form by TACE.…”
Section: Discussionmentioning
confidence: 99%